2011
DOI: 10.1002/lary.21355
|View full text |Cite
|
Sign up to set email alerts
|

Image‐guided endoscopic repair of cerebrospinal fluid rhinorrhea by the bath plug grafting technique

Abstract: The bath plug was feasible for repairing the anterior skull base defects but not for all the sphenoid defects. It proved reliable as a single management in cases with normal intracranial pressure. The image-guided navigation overrides, in sensitivity and specificity, other methods of localization of the anterior skull base defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…A total of 26 cohort studies 934 and 6 case series 6,3539 used HRCT in 622 patients. The cohort studies reported a sensitivity of 0.93 (0.65-1.00) (median [IQR]) and specificity of 0.50 (0.00-1.00), while the case series reported a sensitivity of 1.00 (0.79-1.00) and specificity of 1.00 (0.00-1.00).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 26 cohort studies 934 and 6 case series 6,3539 used HRCT in 622 patients. The cohort studies reported a sensitivity of 0.93 (0.65-1.00) (median [IQR]) and specificity of 0.50 (0.00-1.00), while the case series reported a sensitivity of 1.00 (0.79-1.00) and specificity of 1.00 (0.00-1.00).…”
Section: Resultsmentioning
confidence: 99%
“…Office Endoscopy. Four cohort studies 12,14,22,23 and 2 case series 77,78 used endoscopy in 66 patients. The sensitivity of the cohort studies was 0.58 (0.13-1.00).…”
Section: Radionuclide Cisternography (Rnc)mentioning
confidence: 99%
“…Very few papers have been published locally, and little is known about the management trends of CSF rhinorrhea in Saudi Arabia [17][18][19]. In this retrospective cohort, we aim to present the nine-year experience of a major tertiary center elucidating the etiologies, management, and outcomes of CSF rhinorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies [7,8] on CSF rhinorrhea have been conducted in Saudi Arabia. At King Abdulaziz University Hospital (KAUH), there are no available data on the etiology, diagnosis and management of this condition.…”
Section: Introductionmentioning
confidence: 99%